Selective binding to monoamine oxidase A: In vitro and in vivo evaluation of 18F-labeled β-carboline derivatives. Issue 3 (1st February 2015) - Schieferstein, Hanno; Piel, Markus; Beyerlein, Friderike; Lüddens, Hartmut; Bausbacher, Nicole; Buchholz, Hans-Georg; Ross, Tobias L.; Rösch, Frank
Graphical abstract: Abstract: In this study we synthesized four different 18 F-labeling precursors for the visualization of the monoamino oxidase A using harmol derivatives. Whereas two are for prosthetic group labeling using [ 18 F]fluoro- d 2 -methyl tosylate and 2-[ 18 F]fluoroethyl-tosylate, the other three precursors are for direct nucleophilic 18 F-labeling. Additionally the corresponding reference compounds were synthesized. The syntheses of [ 18 F]fluoro- d 2 -methyl-harmol and 2-[ 18 F]fluoroethyl-harmol were carried out using harmol as starting material. For direct nucleophilic 18 F-labeling of the tracers carrying oligoethyled spacers (PEG), a toluenesulfonyl leaving group was employed. The radiolabeling, purification and formulation for each tracer was optimized and evaluated in vitro and in vivo. Stability tests in human serum showed that all tracers were stable over the observation period of 60 min. μPET studies using of the synthesized tracers revealed that the tracers carrying PEG spacers showed no sufficient brain uptake. Consequently, the 18 F-fuoro alkylated tracers [ 18 F]fluoro- d 2 -methyl-harmol and 2-[ 18 F]fluoroethyl-harmol were further evaluated showing SUVs in the brain of 1.0 ± 0.2 g/mL and 3.4 ± 0.5 g/mL after 45 min, respectively. In blockade studies the selectivity and specificity of both tracers were demonstrated. However, for [ 18 F]fluoro- d 2 -methyl-harmol a rapid washout from the brain was also observed. In vitro binding assays revealed that 2-[ 18 F]fluoroethyl-harmol (IC50 = 0.54 ± 0.06 nM) has a higher affinity than the 18 F-fluoro- d 2 -methylated ligand (IC50 = 12.2 ± 0.6 nM), making 2-[ 18 F]fluoroethyl-harmol superior to the other evaluated compounds and a promising tracer for PET imaging of the MAO A.